P2X3 receptors contribute to transition from acute to chronic muscle pain - Jorge, Carolina Ocanha; de Azambuja, Graciana; Gomes, Beatriz Botasso; Rodrigues, Hayla Lourenço; Luchessi, Augusto Ducati [UNESP]; de Oliveira-Fusaro, Maria Cláudia Gonçalves (Springer Nature, 2020)
This study aimed to evaluate whether the development and/or maintenance of chronic-latent muscle hyperalgesia is modulated by P2X3 receptors. We also evaluate the expression of P2X3 receptors and PKCε of dorsal root ganglions during these processes. A mouse model of chronic-latent muscle hyperalgesia, induced by carrageenan and evidenced by PGE2, was used. Mechanical muscle hyperalgesia was measured by Randall-Selitto analgesimeter. The involvement of P2X3 receptors was analyzed by using the selective P2X3 receptors antagonist A-317491 by intramuscular or intrathecal injections. Expression of P2X3 and PKCε in dorsal root ganglion (L4-S1) were evaluated by Western blotting. Intrathecal blockade of P2X3 receptors previously to carrageenan prevented the development and maintenance of acute and chronic-latent muscle hyperalgesia, while intramuscular blockade of P2X3 receptors previously to carrageenan only reduced the acute muscle hyperalgesia and had no effect on chronic-latent muscle hyperalgesia. Intrathecal, but not intramuscular, blockade of P2X3 receptors immediately before PGE2, in animals previously sensitized by carrageenan, reversed the chronic-latent muscle hyperalgesia. There was an increase in total and phosphorylated PKCε 48 h after the beginning of acute muscle hyperalgesia, and in P2X3 receptors at the period of chronic muscle hyperalgesia. P2X3 receptors expressed on spinal cord dorsal horn contribute to transition from acute to chronic muscle pain. We also suggest an interaction of PKCε and P2X3 receptors in this process. Therefore, we point out P2X3 receptors of the spinal cord dorsal horn as a pharmacological target to prevent the development or reverse the chronic muscle pain conditions.
Keywords: Hyperalgesia; Muscle; P2X3 receptors; PKC epsilon